Pengetahuan Lokal dan Keanekaragaman Tumbuhan Berguna Pada Masyarakat Batulanteh, Pulau Sumbawa, Nusa Tenggara Barat: Sebuah Kajian Etnobotani - Mulyati Rahayu; Nissa Arifa; Muhamad Nikmatullah; Ary Prihardhyanto Keim (Journal of Tropical Ethnobiology, 2020)
The study was conducted in Batulanteh District, Sumbawa regency, Sumbawa Island, West Nusa Tenggara, which is aimed to reveal the knowledge of the Samawa people on the diversity of useful plants and their uses. It documented 111 plant species, in which 47.5% are used as traditional medicine. Also, the sudy found that wild honey bees (Apis dorsata) is having a conspicuous association with plants in producing natural honey, which plays an important role in the local economy. The interviews with selected respondents showed that the Samawa people totally understand the importance of forest conservation in relation with the existence of the honey bees’ life.